(3CYdGe GdfHhIs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3eMeO SYjO GdMSfi GdbOSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GMce eG Ndb hbOQ ahLH Cf jhVM ef GKHGJ GdfHhI eG jfJai YfO GJjGf eZQhQ hLYdJ eG JVef gPG GdcJGH eTJedkG Ydi GMO hYTQjf HGHkG s
(3BNQgG (B:s
(3aCeG CMcGe LgGOg ai MQHI hZRhGJg aSfPcQg ai cJGH HeaQOg ai SjQJg fhVM ajgG ehGbY GYdGeI heHGOj GMcGeI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs